COVID-19: UK frontline intensivists' emerging learning. (August 2021) - Montgomery, Hugh; Rehill, Niran; Camporota, Luigi; Credland, Nicki; Grocott, Mike; Hamilton, Mark; Martin, Daniel; Patel, Brijesh; Suntharalingam, Ganesh; Szakmany, Tamas; Uddin, Shahana; Vercueil, Andre; et al.
The Intensive Care Society held a webinar on 3 April 2020 at which representatives from 11 of the most COVID-19 experienced hospital trusts in England and Wales shared learning around five specific topic areas in an open forum. This paper summarises the emerging learning and practice shared by those frontline clinicians.